ANALISIS PENGGUNAAN LKPD BERBASIS SIKAP PEDULI LINGKUNGAN DALAM PEMBELAJARAN IPA DI SEKOLAH DASAR - Rahmawati, Debby; Fadlillah, M. (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
This research aims to present the results of analyzing the use of LKPD in Science education at elementary schools, aiming to enhance student engagement in the learning process and foster collaboration, critical thinking, and creativity. The research methodology employed a descriptive approach within qualitative research. Qualitative data were gathered from teacher and student responses as users of the educational materials, as well as through observational studies of the learning process and documentation, encompassing the materials used and photos of the learning activities. The study found that the LKPD instructional materials were meticulously designed using the Canva application to create visually appealing and contextually relevant displays concerning environmental issues, while emphasizing student engagement and its relevance to everyday life. The integration of sustainability principles, readability, and optimal accessibility became the focal points in developing the LKPD. Teacher responses indicated high satisfaction with the effectiveness of the LKPD in facilitating learning, while student responses highlighted their enthusiasm and solid understanding of environmental topics. Analysis of student comprehension demonstrated an enhancement in understanding environmental concepts and strong learning outcomes across various activities, with all students achieving the expected learning standards. These results reflect the success of the LKPD in facilitating understanding, interest, and positive responses among students towards environmental issues.